Dynamics of the US-China Trade War: Evolution and Consequences (Economic and Political Thought, 2023)
The trade war between the United States and China, initiated in 2018, hasdestabilized global trade and economy. Despite the signing of the so-calledPhase One Agreement in January 2020, the effects of this economic confrontationextend far beyond its immediate consequences. This article reviewsthe early consequences of the trade war, drawing on analyses from availablesources, taking into account the latest events and data to assess the conflict’simpact on the global economy. Particular attention is paid to recent changesin the trade policies of both countries and their impact on global supply chainsand economic outcomes, emphasizing the long-term implications for theglobal trade order and economic growth.
Keywords: trade war, international trade, tariffis